Effectiveness and safety of a program for appropriate urinary catheter use in stroke care: A multicenter prospective study. Issue 4 (10th October 2021) - Ikeda‐Sakai, Yasuko; Kubo, Kenji; Wada, Mikio; Seki, Rieko; Hijikata, Yasukazu; Yoshioka, Takashi; Takahashi, Yoshimitsu; Nakayama, Takeo
Abstract: Objectives: Since patients with stroke frequently develop bladder dysfunction, a careful approach is required to reduce unnecessary indwelling urinary catheter (IUC) for preventing catheter‐associated urinary tract infection (CAUTI). This study aimed to assess the effectiveness and safety of a program to promote appropriate IUC use in stroke care. Methods: We conducted a prospective interrupted time series study in three tertiary care hospitals in Japan. Adult patients with acute stroke were eligible. The study consisted of three phases: baseline, education and implementation. Our program included an assessment of IUC indications, educational meetings among healthcare professionals, reminders for removal of inappropriate IUC and a urinary retention protocol. The primary outcome was the proportion of inappropriate IUC use to assess effectiveness. The device utilization ratio and incidence of CAUTI were examined to assess effectiveness, and incidences of urinary retention and all symptomatic urinary tract infection (UTI) were examined to assess safety. Results: Among 976 patients who met the inclusion criteria, 738 were analysed. Inappropriate IUC use decreased from 50.1% in the baseline phase to 22.5% in the implementation phase (absolute risk reduction in interrupted time series analysis 42.4% [95% confidence interval, 19.2%–65.6%]). The device utilization ratio decreased from 0.302 to 0.194 ( p < 0.001), whereas CAUTI did not change significantly (from 8.81 to 8.28 per 1000 catheter‐days; incidence rate ratio 0.95 [0.44–1.94]). All symptomatic UTI decreased from 9.5% to 4.9% ( p = 0.015), with no increase in urinary retention. Conclusions: Our program improved the appropriateness of IUC use in stroke care while ensuring safety.